Analisis Pengelolaan Dana Desa Dalam Upaya Meningkatkan Pembangunan dan Kesejahteraan Masyarakat di Desa Lasarabaene - Siska Etika Rahmat Waruwu (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This research is intended to analyze village money management in an effort to improve Lasarabaene's development and welfare. The direction of this research is to find out Lasarabaene's income and expenses from 2018-2022 which are sourced from Lasarabaene's income and expenditure budget reports. The data review process applied in this study is a qualitative data review. The results of this study show that the implementation of the Lasarabaene funds from 2018-2022 has been managed effectively with a percentage rate of 100%, the planning stage from management stage starting, stage implementation, stage administration, stage reporting, and stage accountability. Keywords: Management of village funds, development, effectiveness, welfare